2008
DOI: 10.3102/0162373708319184
|View full text |Cite
|
Sign up to set email alerts
|

Small High Schools on a Larger Scale: The Impact of School Conversions in Chicago

Abstract: This study examines 4 years of small school reform in Chicago, focusing on schools formed by converting large traditional high schools into small autonomous ones. Analyzing systemwide survey and outcome data, the authors assess the assumptions embedded in the reform’s theory of change. They find that these schools are characterized by more collegial and committed teacher contexts and more academically and personally supportive student contexts. There is some evidence of decreased dropout rates and increased gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 14 publications
5
66
0
Order By: Relevance
“…Early research on small schools showed some positive outcomes for low-income students (Howley, 1995;Lee & Smith, 1997) and other students in general (Cotton, 1996(Cotton, , 2001Page, Layzer, Schimmenti, Bernstein, & Horst, 2002;Wasley et al, 2000), more current research is not so clear. Results from the research on small high schools have not been consistently positive as Kahne, Sporte, de la Torre, and Easton (2008) presented in their evaluation of the Chicago High School Redesign Initiative. They found the following:…”
Section: Redefine Professionalismmentioning
confidence: 87%
“…Early research on small schools showed some positive outcomes for low-income students (Howley, 1995;Lee & Smith, 1997) and other students in general (Cotton, 1996(Cotton, , 2001Page, Layzer, Schimmenti, Bernstein, & Horst, 2002;Wasley et al, 2000), more current research is not so clear. Results from the research on small high schools have not been consistently positive as Kahne, Sporte, de la Torre, and Easton (2008) presented in their evaluation of the Chicago High School Redesign Initiative. They found the following:…”
Section: Redefine Professionalismmentioning
confidence: 87%
“…Reforms, such as reducing the size of high schools (e.g., the small schools movement) and improving student-teacher relationships (e.g., advisory programs), abound (Cotton 1996;Darling-Hammond et al 2002a, b). Yet, despite reformers' efforts, the work remains disconnected from classrooms and kids' voices, often focusing on improving teacher culture and personalization, with less attention to curriculum and instruction, and the learning needs of young adolescents (Lee et al 2000;Kahne et al 2008). This is particularly troubling given that effective learning environments are critical to motivating young people to be active members of the classroom and achieve at high levels (Marks 2000;Newmann 1992;Newmann and Wehlage 1993;Nystrand and Gamaron 1991;Steinberg and Allen 2002).…”
Section: The Disengagement Of American Youth In Educationmentioning
confidence: 99%
“…The small but positive significance of school size runs counter to what others have found with regard to school size. Results from the research on small high schools have not been consistently positive as [42] presented in their evaluation of the Chicago High School Redesign Initiative. They found the following: (a) small schools did not offer a stronger instructional climate, (b) nor did these small schools improve student achievement, and (c) students also reported very different experiences and degrees of success as a result of the school they attended.…”
Section: School Level-collegementioning
confidence: 99%